The Use of Literary Adaptations in the EFL Classroom: A Case Study - Beloufa, Chahra (Faculty of Education and Teacher Training of IAIN Palopo, 2023)
The marriage of the two arts, literature and cinema, gave birth to the production of literary adaptations, which is inspiring to explore in an EFL (English as Foreign Language) literature classroom because EFL students are becoming reluctant readers with limited critical literacy. Literary texts in print might cause a loss of interest in literature class. That is why the teacher has always secured material that will keep students' learning literature an enjoyable experience. The researcher experimented on a group of fourth-year English classical system students at Djilali Liabes University, Sidi Bel Abbes, Algeria, to bring about a change. In their British Literature classroom, one projected